USE OF ENZYME PREPARATIONS IN COMPOUND FEED FOR DUCKLINGS - Sherne Vitaliy Sergeevich,; Aubakirov Khamit Abilgazievich,; Lavrentiev Anatoly Yurievich,; Semenov Vladimir Grigoryevich,; Baimukanov Dastanbek Asylbekovich, (Scientific Journal of Pedagogy and Economics, 2020)
The paper presents the results of the influence of enzyme (ferment) preparations in various combinations on the dynamics of growth and development and slaughter qualities of ducklings. The scientific and economic experience was conducted in the Chuvash Republic. For carrying out experiments 3 groups of ducklings on 50 heads in everyone were selected and formed. Ducklings of the 1st experimental group received enzyme preparations amylosubtilin in the amount of 0.05 kg/t and protosubtilin in the amount of 0.05 kg/t during the entire period of growing together with feed. Ducklings for the 2nd experimental group of compound feed were enriched with enzyme preparations amylosubtilin in the amount of 0.1 kg/t and celloviridin in the amount of 0.075 kg/t. It was found that ducklings receiving enzyme preparations in addition to feed had increased growth energy throughout the experiment. By the end of the experiment, the live weight of ducks of the control group was 3,424 kg, the first experimental group receiving in addition to the feed enzyme preparations amylosubtilin in an amount of 0.05 kg/t and protosubtilin in the amount of 0.05 kg/t – 3,712 lbs. In the second experimental group, where the ducks advanced to the feed received enzyme preparations amylosubtilin in the amount of 0.1 kg/t and celloviridin in the amount of 0.075 kg/t, live weight to the end of the experiment amounted to 3,804 kg. The average daily live weight gain of animals in the control group was 53.52 g, and in the first experimental group - 58,10 g, in the second one - 59,56 g. The inclusion of a mixture of enzyme preparations with a compound feed of the experimental animals have contributed to the increase in body length compared to the control on average by 0.9 cm and 1.6 cm, length of tarsus by 2.5 cm and 4.3 cm, chest girth by 1.8 cm and 2.5 cm, respectively. The increased productivity of ducklings in growth was reflected in the reduction of feed costs and unit costs, which contributed to multiplying profits in the experimental groups.